R&D Based Islamic Religious Education Learning Strategy: Types of Models and Their Role - Diana, Zuhur; Kumala, Siti Fatmawati; Sutiah, Sutiah (Wahana Pendidikan, 2025)
The dynamics of education are always faced with problems, both related to government policy and other aspects of the educational component itself. Teachers' problems in teaching, starting from the use of media, methods, and the evaluation process, still often encounter obstacles. Researchers can overcome problems and find solutions scientifically through research and development (R&D). The purpose of writing this article is to explain the R&D research model along with its type and role in PAI learning that requires innovation in the understanding and practice of Islamic values.The data collection method uses library research with data analysis techniques through the process of data collection, data reduction, data presentation, and drawing conclusions. The results of this research show that the R&D model is a research method that focuses on developing products in the form of media or methods to improve the quality of learning. There are various types of R&D development models, including the Borg and Gall model, the Sadiman model, the ADDIE model, the Dick & Carey model, and the Ministry of National Education's Pustekkom model. Each development model has steps that are arranged systematically and structured. In general, these types of R&D models have steps that include problem analysis, product development design, implementation, and evaluation. Regarding the implementation, researchers sometimes modify the development model into simpler steps based on needs analysis.